Code-Switching Strategies: Prosody and Syntax - Torres Cacoullos, Rena (Frontiers in Psychology, 2020)
The contentious question of bilingual processing cost may be recast as a fresh question of code-switching (CS) strategies—quantitative preferences and structural adjustments for switching at particular junctures of two languages. CS strategies are established by considering prosodic and syntactic variables, capitalizing here on bidirectional multi-word CS, spontaneously produced by members of a bilingual community in northern New Mexico who regularly use both languages (Torres Cacoullos and Travis, 2018). CS strategies become apparent by extending the equivalence constraint, which states that bilinguals avoid CS at points of word placement conflict (Poplack, 1980), to examine points of inconsistent equivalence between the languages. Such sites of variable equivalence are junctures where the word strings of the two languages are equivalent only sometimes due to language-internal variable structures. A case in point for the English-Spanish language pair is the boundary between main and complement clauses, where a conjunction occurs always in Spanish but variably in English. The prosodic distancing strategy is to separate the juncture of the two languages. Here the complement clause appears in a different prosodic unit from the main clause, disproportionately as compared both with monolingual benchmarks and with bilinguals' own unilingual English and Spanish. Prosodic distancing serves to mitigate variable equivalence. The syntactic selection strategy is to opt for the variant that is more quantitatively available and more discourse neutral. Here the preference is for the Spanish complementizer que—regardless of main or complement clause language— which is the more frequent option in bilinguals' combined experience in both their languages, whereas English complementizer that is subject to a number of conditioning factors. Syntactic selection serves to restore equivalence at sites of variable equivalence. Discovery of community CS strategies may spur reconsideration of processing cost as a matter of relative difficulty, which will depend on bilinguals' prosodic and syntactic choices at particular CS sites.